COMPARISON OF BLEEDING-RELATED EVENTS IN PATIENTS WHO RECEIVED PIRTOBRUTINIB WITH AND WITHOUT ANTITHROMBOTIC AGENTS - N Lamanna; CS Tam; W Jurczak; A Kontos; H Konig; AS Ruppert; DE Tsai; AAS Scheliga (Hematology, Transfusion and Cell Therapy, 2023)
Objectives: Bruton tyrosine kinase inhibitors (BTKi) are associated with an increased risk of bleeding events. Pirtobrutinib, a non-covalent (reversible) BTKi FDA approved for treatment of R/R MCL after 2 lines of therapy including a BTKi, demonstrated efficacy and tolerability across multiple B-cell malignancies. The incidence of bleeding events in pts treated with pirtobrutinib and concomitant antithrombotic therapy have not been specifically reported. We analyze bleeding events in pts from BRUIN who received pirtobrutinib with antithrombotic therapy. Material and methods: Pts with B-cell malignancies (317 CLL, 166 MCL, 290 other) who enrolled in the open-label, multicenter Phase 1/2 BRUIN study (NCT03740529) were analyzed. Concomitant antithrombotic therapy (direct factor XA inhibitors, heparin anticoagulants, platelet aggregation inhibitors) at time of enrolment was permitted (excluding warfarin). Pirtobrutinib was administered once daily in 28-day cycles) until disease progression or discontinuation due to toxicity. Common Terminology Criteria for Adverse Events V5.0 were used to determine grade and type of bleeding events. Descriptive analyses were performed. Results: As of 29 July 2022, 773 pts received at least 1 pirtobrutinib dose of pirtobrutinib monotherapy, including 216 with concomitant antithrombotic therapy (median age: 72 years [IQR 65-77]and the proportion who were ≥75 years: 34%). Median time on pirtobrutinib with and without antithrombotic therapy was 10.6 (IQR 4.0-19.9) and 9.3 months (IQR 3.1-17.3). Any-grade bleeding events were reported in 44.9% (97/216) pts with antithrombotic therapy vs 32.5% (181/557) without. Most bleeding events (>90%) in both groups were grade ≤2. The most common bleeding events (≥3%) in pts with antithrombotic therapy were contusion (22.7%), hematuria (5.6%), epistaxis (5.1%), petechiae (3.7%), and hematoma (3.2%). Of the 6 (2.8%) pts on antithrombotic therapy with a grade3 bleeding event, 2 (0.9%) were deemed related to pirtobrutinib by investigators: an upper GI bleeding with anemia and a hemarthrosis from a knee injury (1each). Grade≥3 bleeding events occurred in 11 (2%) pts not taking antithrombotics. Any-grade hemorrhage/hematoma occurred in 13/79 (16.5%) pts who received direct factor XA inhibitors, 10/39 (25.6%) who received heparins and 18/112 (16.1%) who received platelet aggregation inhibitors (some received >1 class). Among pts with antithrombotic therapy, median time to onset of any-grade bleeding event was 8.1 weeks (IQR 2.6-24) and median duration of a bleeding event was 2.1 weeks (IQR 0.6-4.3). Among pts who received antithrombotic therapy, bleeding events required dose interruption of pirtobrutinib in 5 pts (2.3%) and no bleeding events led to dose reduction or permanent discontinuation of pirtobrutinib. Conclusion and discussion: Concomitant antithrombotic therapy with pirtobrutinib was associated with an increased rate of bleeding events relative to pirtobrutinib alone, though most events were grade ≤2. High-grade bleeding events were infrequent (<2%). This supports the safety of pirtobrutinib administration in pts requiring antithrombotic therapies. Previously presented at EHA 2023.